2017
DOI: 10.1155/2017/1043836
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Anti-Human Leukocyte Antigen Antibodies Predict Prolonged Isolated Thrombocytopenia and Inferior Outcomes of Haploidentical Hematopoietic Stem Cell Transplantation

Abstract: Prolonged isolated thrombocytopenia (PT) after allogeneic stem cell transplantation (allo-SCT) has a great impact on transplant outcome. In this study, we performed a retrospective analysis to investigate the association of donor-specific anti-human leukocyte antigen (HLA) antibodies (DSAs) with PT in 394 patients who underwent unmanipulated haploidentical blood and marrow transplantation (HBMT). For HLA antibody positive samples with a median fluorescent intensity (MFI) > 500, DSAs were further examined. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…We also observed that the patients in FDMR CRD group showed low platelet engraftment rate, and the risk of platelet engraftment failure of FDMR CRD group was significantly higher than that of MD group. Zhao et al [32] observed that compared to cases with prolonged thrombocytopenia, patients without prolonged thrombocytopenia had lower incidence of NRM (16.3% vs. 32.5%, P = 0.043), higher probabilities of DFS (74.7% vs. 56.3%, P = 0.046) and OS (75.2% vs. 56.3%, P = 0.047) after haplo-HSCT. Multivariate analysis showed that the onset of prolonged thrombocytopenia was independently associated with NRM (HR = 2.7; P = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the patients in FDMR CRD group showed low platelet engraftment rate, and the risk of platelet engraftment failure of FDMR CRD group was significantly higher than that of MD group. Zhao et al [32] observed that compared to cases with prolonged thrombocytopenia, patients without prolonged thrombocytopenia had lower incidence of NRM (16.3% vs. 32.5%, P = 0.043), higher probabilities of DFS (74.7% vs. 56.3%, P = 0.046) and OS (75.2% vs. 56.3%, P = 0.047) after haplo-HSCT. Multivariate analysis showed that the onset of prolonged thrombocytopenia was independently associated with NRM (HR = 2.7; P = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of possible immunized donors and female‐to‐male mismatches were also similar between Cobe and Optia (Table ). Other studies have shown a potential effect of DSA on clinical outcomes after HSCT . We have no method in our clinical setting for the detection of DSA against minor antigens.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have shown a potential effect of DSA on clinical outcomes after HSCT. 35,36 We have no method in our clinical setting for the detection of DSA against minor antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of DSAs is also associated with increased NRM. Zhao et al also found that the presence of DSAs increased the occurrence of prolonged thrombocytopenia after haplo‐HCT …”
Section: Donor‐specific Anti‐hla Antibodiesmentioning
confidence: 95%